Analysis of the Correlation Between English Language Proficiency and the Professional Readiness of Students in Teacher Education Study Programs in Entering the Workforce - Mella Narolita; Sari Rahayu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the correlation between English language proficiency and the professional readiness of students in teacher education study programs for entering the workforce. Students in teacher education study programs in Indonesia generally focus on mastering subject matter according to their respective fields, while English language skills are often considered supplementary. Current developments in the workforce demand graduates who are capable of adapting globally, including within international educational environments and non-school sectors. The method used in this study was a descriptive quantitative approach through the distribution of questionnaires completed by students in teacher education study programs at several higher education institutions. The research results indicate that among five higher education institutions in West Java, 42% of respondents strongly agree and 35% agree that English is an essential skill that needs to be mastered, while 15% remain neutral because they consider English proficiency not yet urgent when subject mastery is still low. These findings confirm that English language proficiency plays a role in enhancing the professional readiness of students and therefore needs to be more strategically integrated into the higher education curriculum, particularly in teacher education study programs.